Potencial antioxidante nos vinhos Tannat comerciais em Dom Pedrito - (:unkn) unknown (Universidade Federal do Pampa, 2018)
The Campanha region is located in the southwest of Rio Grande do Sul, on the border between Brazil and Uruguay, where it stands out due to its high oenological potential. The Municipality of Dom Pedrito-RS gains evidence with the recognition of the wines produced, and especially the cultivar Tannat, which stands out for the high potential (besides the sensorial and physical chemical characteristics of each variety, the amount of tannins and anthocyanins present and the index polyphenols), which gives the wine its wines and easy adaptation to climatic conditions (with a drier climate during the ripening period of grapes, soils and terrain capable of optimizing the quality of the raw material, as well as a great thermal amplitude and optimum luminosity, favoring the full ripening of the fruits). The objective of the present work was to evaluate the antioxidant potential of the Tannat wines produced in the municipality of Dom Pedrito. For this, three samples of wines of the Tannat cultivar originated from the municipalities' wineries were analyzed. The antioxidant capacity of the wines was evaluated using the free radical sequestration method of 2,2diphenyl-1-picrylhydrazyl (DPPH), the concentration of total phenols was determined by the Flin-Ciocalteau colorimetric method. total phenols were found to be 379.89 mg.100ml-1 of gallic acid, referring to the T1 sample resembling the concentrations found in the literature. Based on the data presented in the present work, it is concluded that the wines of the cultivar Tannat have a high antioxidant capacity. Further studies of this cultivar should be carried out to enrich the knowledge of the quality of the wines produced in the region of the Rio Grande do Sul Campaign.
Keywords: Atividade antioxidade; Fenóis totais; Campanha Gaúcha; Dom Pedrito; Antioxidant activity; Gaucho Campaign; CNPQ::CIENCIAS AGRARIAS